A common data language for clinical research studies: the National Institute of Neurological Disorders and Stroke and American Academy for Cerebral Palsy and Developmental Medicine Cerebral Palsy Common Data Elements Version 1.0 recommendations. (15th March 2018) - Schiariti, Verónica; Fowler, Eileen; Brandenburg, Joline E; Levey, Eric; Mcintyre, Sarah; Sukal‐Moulton, Theresa; Ramey, Sharon L; Rose, Jessica; Sienko, Susan; Stashinko, Elaine; Vogtle, Laura; Feldman, Robin S; et al.
Abstract : To increase the efficiency and effectiveness of clinical research studies, cerebral palsy (CP) specific Common Data Elements (CDEs) were developed through a partnership between the National Institute of Neurological Disorders and Stroke (NINDS) and the American Academy of Cerebral Palsy and Developmental Medicine (AACPDM). International experts reviewed existing NINDS CDEs and tools used in studies of children and young people with CP. CDEs were compiled, subjected to internal review, and posted online for external public comment in September 2016. Guided by the International Classification of Functioning, Disability and Health framework, CDEs were categorized into six domains: (1) participant characteristics; (2) health, growth, and genetics; (3) neuroimaging; (4) neuromotor skills and functional assessments; (5) neurocognitive, social, and emotional assessments; and (6) engagement and quality of life. Version 1.0 of the NINDS/AACPDM CDEs for CP is publicly available on the NINDS CDE and AACPDM websites. Global use of CDEs for CP will standardize data collection, improve data quality, and facilitate comparisons across studies. Ongoing collaboration with international colleagues, industry, and people with CP and their families will provide meaningful feedback and updates as additional evidence is obtained. These CDEs are recommended for NINDS‐funded research for CP. What this paper adds: This is the first comprehensive Common Data Elements (CDEs) for children and young people with CP for clinical research. The CDEs for children and young people with CP include common definitions, the standardization of case report forms, and measures. The CDE guides the standardization for data collection and outcome evaluation in all types of studies with children and young people with CP. The CDE ultimately improves data quality and data sharing. What this paper adds: This is the first comprehensive Common Data Elements (CDEs) for children and young people with CP for clinical research. The CDEs for children and young people with CP include common definitions, the standardization of case report forms, and measures. The CDE guides the standardization for data collection and outcome evaluation in all types of studies with children and young people with CP. The CDE ultimately improves data quality and data sharing. This article is commented on by Fairhurst on page968 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations. Video Podcast:https://www.youtube.com/watch?v=dmYt4vbzioU&feature=youtu.be